(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
Oral diagnosis simply refers to the analysis of the inside of the mouth. Effective treatment of any oral disease is possible only if a correct and accurate diagnosis is made. Oral diagnosis in the field of dentistry involves the examination and detection of all problems inside and outside the oral cavity, as well as finding the relationships between them, using scientific knowledge. Thus, it helps to formulate a final accurate treatment plan based on the findings collected. Effective treatment of any dental problem requires an accurate diagnosis. Diagnosis involves gathering information by collecting analysis and conducting a clinical examination of the patient. This is confirmed by using various diagnostic tools, and more accurate and detailed information is obtained from these diagnostic tools.